The Influence of Transformational Leadership, Interpersonal Communication, and Organizational Conflict On Organizational Effectiveness - Mukhtar Mukhtar; Risnita Risnita; Muhammad Anggung Manumanoso Prasetyo (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
This study investigated whether the effect correlation exists between the Transformational Leadership, Interpersonal Communication, Organizational Conflict and Organizational Effectiveness in dayah in Aceh. Data were collected by questionnaires by 90 teachers in 3 pesantren, analysis using Path Analysis. The study found that the transformational leadership was most frequently employed, followed by the interpersonal communication, and then organizational conflict. The study found a positive effect transformational leadership, interpersonal communication and organizational conflict towards organizational effectiveness. Finally, organizational effectiveness differed according to leadership and communication factors. Suggestions from this research are there is a need to develop the organizational effectiveness by attitude, motivation and technology in utilizing existing resources in the pesantren, dayah program and unit program. Findings of this study also open a new area of research on dayah principalship, performance, and effectiveness in the Aceh Government.